Cognitive Performance in a Subclinical Obsessive-Compulsive Sample 1: Cognitive Functions. (9th July 2013) - Johansen, Thomas; Dittrich, Winand H.
Abstract : Individuals who are not clinically diagnosed with obsessive-compulsive disorder (OCD) but still display obsessive-compulsive (OC) tendencies may show cognitive impairments. The present study investigated whether there are subgroups within a healthy group showing characteristic cognitive and emotional performance levels similar to those found in OCD patients and whether they differ from OCD subgroups regarding performance levels. Of interest are those cases showing subclinical symptomatology. The results revealed no impairments in the subclinical OC participants on the neuropsychological tasks, while evidence suggests that there exist high and low scores on two standardised clinical instruments (Yale-Brown Obsessive Compulsive Scale and Cognitive Assessment Instrument of Obsessions and Compulsions) in a healthy sample. OC symptoms may diminish the quality of life and prolong sustainable return to work. It may be that occupational rehabilitation programmes are more effective in rectifying subclinical OC tendencies compared to the often complex symptoms of diagnosed OCD patients. The relationship between cognitive style and subclinical OC symptoms is discussed in terms of how materials and information might be processed. Although subclinical OC tendencies would not seem to constitute a diagnosis of OCD, the quality of treatment programmes such as cognitive behavioural therapy can be improved based on the current investigation.